Burkina Faso : Second and Third Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criteria and Extension of Commitment Period. (IMF Staff Country Reports; Country Report ;, 2005)
Burkina Faso's Second and Third Reviews Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criteria are examined. Fiscal policy for 2005 aims at preserving social sector outlays while ensuring that the external debt burden falls. Structural reforms are the key to achieving higher rates of economic growth and sustained poverty reduction, and the authorities place particular emphasis on reforms in the public utilities.